Modeling the potential influence of economic migration on Ebola virus disease transmission dynamics - Diane Djiomba Njankou, Sylvie; Nyabadza, Farai (Frontiers in Applied Mathematics and Statistics, 2023)
The good health of the economy of developed countries is an attracting factor for economic migrants from poorer countries whose movements can be associated with the spread of diseases such as the Ebola virus disease. In this paper, we formulate a model of Ebola virus disease that considers two patches with different economic statuses represented by the respective gross-national incomes of the two patches. First, we consider a one-directional movement from a poorer patch to a rich patch. Second, we consider a two-way migration model where people move between patches. The steady states of the model are determined and analysed. The analysis shows also that the disease free and the endemic equilibrium points are locally stable. The analysis also shows that a unique endemic equilibrium point exists in the poor patch when the reproduction number in this patch is greater than one and multiple endemic equilibria exist in the rich patch when the reproduction number in the poor patch is less than one. The model dynamics of the rich patch present a backward bifurcation which does not facilitate easy Ebola virus disease control. Sensitivity analysis is carried out to determine the most sensitive parameters that must be carefully estimated for the successful control of the Ebola virus disease. Numerical simulations indicate a decrease in the number of infected individuals in the rich patch when movements of populations are limited through the improvement of the economy in the poor patch. So, the improvement of the economy of poorer countries may be critical in avoiding potential outbreaks of Ebola virus disease.